ASSESSING THE CORRELATION BETWEEN VISCERAL FAT AREA AND PERITONEAL DIALYSIS IN A CLINICAL CONTEXT: A PROSPECTIVE STUDY - Prasad, Dharmendra; Shankar, Vijay; Kishore, Rishi (Student's Journal of Health Research Africa, 2023)
Aim: In this prospective study, the sequential alterations in adipose tissue composition and nutritional status were examined. Also, the factors linked to the increase in adipose mass among patients undergoing peritoneal dialysis (PD) were analyzed. Methods: The evaluation of body composition was conducted using bioelectric impedance analysis (BIA) and computed tomography (CT) imaging techniques. The evaluation of the individual's nutritional status was conducted using the Subjective Global Assessment (SGA), protein equivalent of nitrogen appearance (nPNA), serum albumin levels, C-reactive protein (CRP) levels, and lipid profile. All measurements, with the exception of Bioelectrical Impedance Analysis (BIA), were conducted on the seventh day and at 6 and 12 months following the initiation of Peritoneal Dialysis (PD). Results: A total of 60 participants were recruited for the study. There was a progressive rise in body weight observed over the course of 12 months. Individuals who exhibited a higher quantity of visceral adipose tissue at the initiation of peritoneal dialysis experienced a reduced accumulation of visceral adipose tissue within the initial 6-month period (correlation coefficient = -0.821, p-value = 0.002). Patients with a higher initial subcutaneous fat mass demonstrated a lower increase in subcutaneous fat mass (correlation coefficient = -0.709, p-value = 0.015) during the course of peritoneal dialysis (PD). Conclusion: Patients initiating peritoneal dialysis (PD) commonly encounter an increase in body weight, encompassing both visceral and subcutaneous adipose tissue, within the initial six-month period of commencing PD therapy. Recommendation: Accumulation of visceral fat is recommended to be measured by magnetic resonance imaging or CT, which can distinguish fat from other tissues and allow the measurement of visceral and subcutaneous abdominal fat mass independently with high reproducibility.